Outcome Measures in Clinical Trials of Patients With Myasthenia Gravis - Thomsen, Jan Lykke Scheel; Andersen, Henning (Frontiers in Neurology, 2020)
Myasthenia gravis (MG) is a heterogeneous disorder whose clinical presentation ranges from mild ocular deficits to severe widespread weakness. This variance poses a challenge when quantifying clinical deficits. Deficits and symptoms are quantified using standardized clinical scales and questionnaires which are often used as outcome measures. The past decades have seen the development of several validated outcome measures in MG, which are used in clinical trials to obtain regulatory approval. In recent years, emphasis has moved from objective assessments to patient-reported outcomes. Despite a growing body of literature on the validity of the MG-specific outcome measures, several unresolved factors remain. As several novel therapeutics are currently in clinical development, knowledge about capabilities and limitations of outcome measures is needed. In the present paper, we describe the most widely used clinical classifications and scales in MG. We highlight the choice of outcome measures in published and ongoing trials, and we denote whether trial efficacy was reached on these outcomes. We discuss advantages and limitations of the individual scales, and discuss some of the unresolved factors relating to outcome assessments in MG.